Determinant Factors Influencing Public Intention to Visit Griya Sehat at the UPT Laboratory of Herbal Materia Medica Batu - Wijaya, Moch Naufal; Suhita, ,Byba Melda; Nurwijayant i (International Journal of Science and Society, 2025)
Traditional health services are increasingly recognized as essential components of promotive and preventive health care in Indonesia. One such facility is Griya Sehat at the UPT Laboratory of Herbal Materia Medica Batu, which offers various therapies including acupressure, cupping, and standardized herbal medicines. Despite this potential, visitation rates remain below institutional expectations. This study aimed to examine the influence of knowledge, service quality, and infrastructure on public intention to visit the facility. A quantitative analytic study with a cross-sectional design was conducted among 170 respondents recruited through purposive sampling. Data were collected using structured questionnaires and analyzed with ordinal logistic regression. Assumption testing was performed prior to analysis, including multicollinearity diagnostics and the test of parallel lines to assess the proportional odds assumption. The findings showed that all three predictors significantly influenced visiting intention. Knowledge had a positive effect (β = 0.205; p = 0.001), indicating that respondents with greater awareness of traditional therapies were more likely to report stronger intention to visit. Service quality also contributed significantly (β = 0.115; p < 0.001), with responsiveness, empathy, and professional assurance being the most valued dimensions. Among the predictors, infrastructure was the most dominant determinant (β = 0.546; p < 0.001), with respondents highlighting cleanliness, equipment readiness, and comfort as strengths, while temperature, lighting, and navigation were identified as areas needing improvement. Model evaluation indicated good fit, with a Nagelkerke R² value of 0.664, suggesting that the predictors explained approximately two-thirds of the variance in visiting intention. In conclusion, enhancing infrastructure, supported by improvements in service quality and community knowledge, is crucial to strengthen public intention to visit Griya Sehat. Strategic recommendations include upgrading physical facilities, improving patient-centered communication, and expanding health promotion to raise awareness of the benefits and safety of traditional health services.